Reproductive Justice Narratives of People with Disabilities: Overturned and Overlooked - Abigail O. Akande; Cameron Manser (International Journal of Disability and Social Justice)
In this narrative analysis, we explored accounts of individuals with disabilities who were parents, who wished to become parents, or who did not have intentions of becoming parents, to shed light on their concerns related to reproductive rights. In 1973, the United States Supreme Court declared abortion to be legal nationwide via the Roe v. Wade decision. Access to abortions provided significant and distinct healthcare services for people with disabilities that have not been sufficiently explored in research. With the overturning of Roe v. Wade in 2022, our goal was to shed light on the stories of people with disabilities and to explore the potential impact of this legislative decision. The reproductive justice framework guided the generation of eight themes: Intersectionality, Advocacy, Legislation, Support Structure, Socioeconomic Status, Emotions, Ethics, and Adopting Children with Disabilities. The authors discuss practical implications and approaches for future research into this critical issue.